Efficient fatigue assessment of ship structural details. (27th May 2020) - Gaidai, Oleg; Storhaug, Gaute; Naess, Arvid; Ye, Renchuan; Cheng, Yong; Xu, Xiaosen
ABSTRACT: Accurate fatigue assessment of ship structures is an important part of the structural reliability. As a result of accumulated fatigue damage, fatigue cracks may occur earlier than expected in critical locations of ocean-crossing ships. In many practical cases, the data set needed for accurate fatigue damage estimation, can be obtained by either numerical simulation or direct measurement, but in practice the size of the above-mentioned data set is often limited and not large enough for accurate direct fatigue damage calculation. The objective of this paper is therefore to contribute to development of novel fatigue estimation techniques that utilise available limited data set more efficiently. The continuous stress time series covering nearly two years duration has been analysed in this paper. Rainflow counting method was subsequently used for the accumulated fatigue damage assessment. An efficient distribution tail extrapolation technique has been proposed to accurately predict fatigue damage. The proposed technique utilises available data more efficiently, than direct fatigue estimation.